Primary Health Care Nurses’ Knowledge about Alcohol Use with Respect to its Impact on Blood Pressure and the Risk of Developing Arterial Hypertension - Grabowska, Hanna; Grabowski, Władysław; Gaworska-Krzemińska, Aleksandra; Grzegorczyk, Michał; Świetlik, Dariusz; Narkiewicz, Krzysztof (Polish Journal of Public Health, 2009)
Introduction. Primary health care (PHC) nurses can play a signifi cant role in reducing the cardiovascular risk, and contribute to lowering alcohol consumption by their patients.  Purpose. Determining the knowledge of PHC nurses about alcohol consumption evaluation and its impact on arterial blood pressure (BP) and the risk of developing hypertension. Material and methods. The study, conducted in 2007-2009, included 185 PHC nurses (aged 23-60, x=40.9, SD=7.12; length of service 1-35 years, x=19.37, SD=7.15). The following methods were employed: diagnostic survey, questionnaire technique and custom survey questionnaire. The statistical analysis used the STATISTICA software package, the assumed signifi cance level being p≤0.05. It took into account the effect of age, domicile, job, place and length of service and forms of postgraduate education on the nurses’ knowledge levels. Results. Knowledge of questionnaire screening tools for evaluating alcohol drinking styles was demonstrated by 15.1% of nurses; 37.3% and 53.5% of the respondents, respectively, correctly interpreted the standard portion and pointed to the alcohol consumption limit. The impact of alcohol consumption on BP was known to 91.9% of PHC nurses. Statistically, correct answers were more frequently given by persons who graduated from bachelor’s degree courses in nursing (p